2015
DOI: 10.1002/path.4493
|View full text |Cite
|
Sign up to set email alerts
|

Stromal matrix metalloproteinase 2 regulates collagen expression and promotes the outgrowth of experimental metastases

Abstract: Breast cancer survival rates decrease from 99% for patients with local disease to 25% for those with distant metastases. Matrix metalloproteinases (MMPs), including MMP2, are associated with metastatic progression. We found that loss of host MMP2 reduces the proliferation of experimental metastases in the lungs and identified fibroblasts in tumour-bearing lungs as the major source of MMP2. In vitro, spheroidal mammary tumour growth was increased by co-culture with control fibroblasts isolated from tumour-beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…To explore the underlying mechanism, we reanalyzed breast cancer data from The Cancer Genome Atlas, which revealed that LOX expression correlates with expression of matrix metallopeptidase 2 (MMP2) (Figure 3A, R 2 = 0.47), collagen type I alpha1 (COL1A1) (Figure 3B, R 2 = 0.47), and secreted protein acidic and rich in cysteine (SPARC) (Figure 3C, R 2 = 0.51). Given that MMP2, COL1A1 and SPARC are all pro-metastatic genes [810], we suggest these genes play crucial roles in LOX+ breast cancer metastasis. In addition, data mining results from The Comparative Toxicogenomics Database indicates that bisphosphonate down-regulates expression of LOX, MMP2, COL1A1 and SPARC, which means bisphosphonate may suppress cancer metastasis by targeting these four genes.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the underlying mechanism, we reanalyzed breast cancer data from The Cancer Genome Atlas, which revealed that LOX expression correlates with expression of matrix metallopeptidase 2 (MMP2) (Figure 3A, R 2 = 0.47), collagen type I alpha1 (COL1A1) (Figure 3B, R 2 = 0.47), and secreted protein acidic and rich in cysteine (SPARC) (Figure 3C, R 2 = 0.51). Given that MMP2, COL1A1 and SPARC are all pro-metastatic genes [810], we suggest these genes play crucial roles in LOX+ breast cancer metastasis. In addition, data mining results from The Comparative Toxicogenomics Database indicates that bisphosphonate down-regulates expression of LOX, MMP2, COL1A1 and SPARC, which means bisphosphonate may suppress cancer metastasis by targeting these four genes.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in microarray results, expression of matrix metalloproteinases (MMPs) 2 and 15 was significantly decreased in TAMs by CDDO-Me treatment. These MMPs are known to be involved in the remodeling of the TME extracellular environment 45,46 and can enhance metastasis in several solid tumors 28,47 . Interestingly, tissue inhibitor of metalloproteinase 2 (TIMP2) was also attenuated by treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2c). Because MMP2 has been implicated in metastatic breast disease 28 , we assessed in vivo CDDO-Me effects on expression of this metalloproteinase. As demonstrated in Fig.…”
Section: Cddo-me Confers Immunostimulatory Transcriptional Activationmentioning
confidence: 99%
“…MMP2 expressed by stromal fibroblasts has also been shown to be important in promoting the growth of metastases in breast cancer [47]. Loss of stromal fibroblast MMP2 reduced the proliferation of metastasis and this was associated with reduced MMP2-induced transforming growth factor beta 1 activity, highlighting the interaction between MMPs and the transforming growth factor pathway [47].…”
Section: Interactions Of Mmps With Pro-invasive Pathwaysmentioning
confidence: 99%